Fabrication and Characterization of Ultra-High-Pressure (UHP)-Induced Whey Protein Isolate/κ-Carrageenan Composite Emulsion Gels for the Delivery of Curcumin - Su, Jiaqi; Wang, Linlin; Dong, Wenxia; Wei, Jiao; Liu, Xi; Yan, Jinxin; Ren, Fazheng; Yuan, Fang; Wang, Pengjie (Frontiers in Nutrition, 2022)
Emulsion gels have attracted extensive interests due to their unique physical characters, remarkable stability and control release properties of flavor and functional components compared to emulsions in liquid. In the current work, whey protein isolate (WPI)/κ-Carrageenan (κ-CG) composite emulsion gels were fabricated based on the ultra-high pressure (UHP) technology, in replace of traditional thermal, acid, or enzyme processing. Uniform composite emulsion gels could be fabricated by ultra-high pressure above 400 MPa with minimum WPI and κ-CG concentrations of 8.0 wt% and 1.0 wt%, respectively. The formation of UHP-induced emulsion gels is mostly attributed to the hydrophobic interaction and hydrogen bonding. Emulsion gels with different textures, rheology properties and microstructures could be fabricated through adjusting the formulations (WPI concentration, κ-CG concentration and oil phase fraction) as well as processing under different conditions (pressure and time). Afterwards, curcumin-loaded emulsion gels were fabricated and subjected to an in-vitro simulated gastrointestinal digestion in order to investigate the gastrointestinal fate of curcumin. In vitro simulated digestion results demonstrated that the UHP-treatment significantly retarded the release of curcumin but had little impact on the bioaccessibility of curcumin. Results in this work provide useful information for the construction of emulsion gels through a non-thermal process, which showed great potential for the delivery of heat-sensitive bioactive components.